2023
DOI: 10.1177/00178969231172131
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of nutrition information on food labels among higher income adults in India

Abstract: Objectives: This study assessed food label reading habits and understanding of nutrition information on food labels by higher income adults in India. Design: It involved a cross-sectional study using non-probability purposive sampling. Setting: Data were collected by mixed methods approach between March 2019 and February 2020. Adults were selected from housing colonies in four geographical zones of Delhi, India. Method: A total of 589 adults (20–40 years) belonging to upper middle-income and high-income groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Annunziata and Vecchio (2012) stated that 48% of people pay attention to food labels when buying a new product, while only 4.3% routinely read them. A more detailed perspective is provided by Mediratta and Mathur (2023), who showed that 76% of higher income adults read nutrition labels, but few can understand all the information correctly. All of these findings suggest that consistent attention to nutrition labels may lead to more use of digital nutrition labeling and online ordering services to make informed food choices and confirm already existent information, regardless of familiarity with the product.…”
Section: Methodsmentioning
confidence: 99%
“…Annunziata and Vecchio (2012) stated that 48% of people pay attention to food labels when buying a new product, while only 4.3% routinely read them. A more detailed perspective is provided by Mediratta and Mathur (2023), who showed that 76% of higher income adults read nutrition labels, but few can understand all the information correctly. All of these findings suggest that consistent attention to nutrition labels may lead to more use of digital nutrition labeling and online ordering services to make informed food choices and confirm already existent information, regardless of familiarity with the product.…”
Section: Methodsmentioning
confidence: 99%